x-2y=0

x=3y+1

For the elimination method, you have to eliminate a variable by adding/subtracting the two equations.

x - 2y = 0

x - 3y = 1 (I subtracted 3y from both sides to get the equations in the same format)

If you subtract equation 2 from equation 1:

-[x-3y = 1]

(x-x) + (-2y +3y) = (0-1)

The x's cancel each other and you're left with:

y = -1

Now, you can substitute y = -1 into one of the equations to solve for x:

x - 2(-1) = 0

x + 2 = 0

x = -2

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up